Prevalence of diabetic nephropathy among Type 2 diabetic patients in some of the Arab countries - Aldukhayel, Abdulrhman (International Journal of Health Sciences, 2017)
Type 2 diabetes mellitus (DM) is a public health concern worldwide and an important cause of morbidity and mortality. Type 2 DM is associated with microvascular and macrovascular complications. Diabetic nephropathy (DN), which is characterized by proteinuria, is one of the most serious long-term microvascular complications of DM. The proportion of DN is increasing worldwide. DN is the leading cause of chronic kidney diseases and end stage renal disease (ESRD), which constitutes the major workload of dialysis centers worldwide. Microalbuminuria is the earliest sign of DN, so the early detection of microalbuminuria and early control of diabetes retards the progression of DN.